Status of root knot nematode disease on kenaf cultivated on BRIS soil in Kuala Terengganu, Malaysia - Tahery, Yaghoob; Ab Shukor, Nor Aini; Abdul Hamid, Hazandy; Abdullah, Mohd Puad; Basherudin, Norlia (IDOSI Publications, 2011)
A field survey was carried out to investigate kenaf plants cultivated in Telaga Papan, Terengganu, Malaysia with respecting to their performance, root galling and growth characteristics. In this investigation, the aims were to assess the status of nematode infection on kenaf planted on this sandy BRIS area and estimate the incidence and severity of infection. Inspection of kenaf plants showed decolorating, drying and wilting of their leaves along with developing of galls on their root. Leaf colour and plant performance were found to be significantly different between infected and control plant. Infection with nematode was detected to reduce height, stalk diameter and number of node in kenaf plants. Root galling severity and percentage of active galls in kenaf roots were calculated as well. They showed to be closely correlated to each other. However, the relation between root galling severity and height was higher than with diameter and number of node.